Incidents and major causes of suicides in India (1997–2007). (1st March 2011) - Deb, S
Abstract : The epidemiology of suicide in India from 1997 to 2007 was explored in order to ascertain the incidence and rates of suicide by gender, age groups, marital status, state, causes and method used for suicide. The study was based on secondary data. About 1 22 637 people lost their lives by committing suicide in India during the year 2007, which means 14 suicides took place every hour. The number of suicides in the country during the last decade recorded an increase of 28.7%. The rate of suicide per 1 lakh population in India was 10.8 during 2007 compared to 10.5 during 2006. In terms of rate of suicide per 1 lakh population, Puducherry reported the highest rate of suicide (48.6), followed by A&N Islands (38.5). The overall male:female ratio of suicide victims for the year 2007 was 65:35. It was observed that 77.5% of the suicide victims were married while 20.8% were unmarried. Family problems and illness accounting for 23.8% and 22.3% respectively were the major causes of suicides among the specified causes. Love affairs (2.8%), bankruptcy (2.7%), poverty (2.3%) and dowry disputes (2.6%) were the other causes driving people towards suicides. In the case of children, failure in examination was one of the main causes of suicide. Suicide by consuming poison (35.0%), hanging (31.7%), self-immolation (8.5%) and downing (6.8%) were the prominent means of committing suicide in India. The findings of the present study suggested multiple approaches for preventing suicidal ideology in India.